2015
DOI: 10.1039/c5ob01473e
|View full text |Cite
|
Sign up to set email alerts
|

Role of keto–enol tautomerization in a chiral phosphoric acid catalyzed asymmetric thiocarboxylysis of meso-epoxide: a DFT study

Abstract: The mechanism of a chiral phosphoric acid catalyzed thiocarboxylysis of meso-epoxide was investigated by density functional theory (DFT) calculations (M06-2X). The nucleophilic ring opening of epoxide by thiobenzoic acid was found to proceed via a concerted termolecular transition state with a simultaneous dual proton transfer to yield the β-hydroxy thioester product. Electrostatic interactions together with the steric environment inside the chiral catalyst play an important role in determining the enantiosele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…52 In 2015, we also reported the importance of C-H•••O interactions for catalyst-substrate binding and to determine the enantioselectivity of a chiral phosphoric acid 11 catalyzed sulfonylation of cyclohexane epoxide (Figure 21). 54 The distortion/interaction analysis showed that the preferred TS is the one that minimizes steric interactions inside the chiral binding pocket of the catalyst.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…52 In 2015, we also reported the importance of C-H•••O interactions for catalyst-substrate binding and to determine the enantioselectivity of a chiral phosphoric acid 11 catalyzed sulfonylation of cyclohexane epoxide (Figure 21). 54 The distortion/interaction analysis showed that the preferred TS is the one that minimizes steric interactions inside the chiral binding pocket of the catalyst.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…2C) and is reminiscent of oxetane, oxirane and aziridine openings. 48,[50][51][52][53][54] As was identied with the model catalyst, protonation happens trans to the azetidine substituent in TS 9 (S) and cis in TS 9 (R) (Fig. 4B and C, top).…”
Section: Resultsmentioning
confidence: 75%
“…For such sp 3 -hybridized carbon electrophiles, fewer experimental reports are known. Computational studies on these systems 48,[50][51][52][53][54] have relied on the optimization of stereodetermining TSs to identify if distortions or non-covalent interactions are the major contributors to selectivity, but few general models have been proposed. 51,54 We were intrigued that DFT studies of organocatalyzed reactions oen provide clear insights about the selectivitydetermining TSs, but rarely yield general models of selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this arrangement of the substrates under the phosphoric acid catalyst is almost identical to what was observed with the model catalyst 5 (compare Figure 4 to Figure 3A-B) and is reminiscent of oxetane, oxirane and aziridine openings. 48,[50][51][52][53][54] As was identified with the model catalyst, protonation happens trans to the azetidine substituent in TS 9 (S) and cis in TS 9 (R) (Figure 4C-D). The cis approach in TS 9 (R) is accompanied by significant puckering of the C3 position in the ring (dihedral angle of 14° in TS 9 (R), only 5° in TS 9 (S)).…”
Section: Resultsmentioning
confidence: 99%
“…For such sp 3 -hybridized carbon electrophiles, fewer experimental reports are known. Computational studies on these systems 48,[50][51][52][53][54] have relied on the optimization of stereodetermining TSs to identify if distortions or non-covalent interactions are major contributor to selectivity, but few general models have been proposed. 51,54 We were intrigued that DFT studies of organocatalyzed reactions often provide clear insights about the selectivity-determining TSs, but rarely yield general models of selectivity.…”
Section: Introductionmentioning
confidence: 99%